2004
DOI: 10.1179/030192304225011115
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity effect of titanium pickup by mould fluxes for stainless steel

Abstract: Mould flux samples from an operating continuous caster showed a steady state increase in titanium oxide content of 3-4% for a titanium stabilised ferritic stainless steel and about 6% for a titanium stabilised austenitic stainless steel. Owing to the reduction of silica the flux basicity increased from 0 . 8 to 0 . 9, and from 0 . 95 to 1 . 2, for the ferritic and austenitic steels, respectively. Similar changes in composition were found for mould shims, which had been recovered from the mould after casting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 11 publications
1
37
1
Order By: Relevance
“…[3][4][5][6][7][8] The viscosity values reported in these references are in most cases considerably higher than those found in the present study. This diversity is attributed to the differences in the chemical compositions.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…[3][4][5][6][7][8] The viscosity values reported in these references are in most cases considerably higher than those found in the present study. This diversity is attributed to the differences in the chemical compositions.…”
Section: Resultscontrasting
confidence: 52%
“…Several experimental studies have earlier been carried out in order to determine viscosity data for mould flux slags, [3][4][5][6][7][8][9][10][11][12] both industrial ones as well as synthetic slags with compositions close to industrial mould fluxes. Almost all mould powders contain CaF 2 as it lowers the viscosity and melting point of the fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers 4,5) have reported that viscosity of mould fluxes decreases with increased pickup of TiO2 in fluxes during casting. According to the present structural study, degree of polymerization is slightly enhanced with TiO2 increase.…”
Section: (A)-5(c) the Summary Of Deconvolution Results Is Listed Inmentioning
confidence: 99%
“…[1][2][3] During the casting of titanium-stabilized stainless steel, titanium in the steel have a tendency to reacting with silica in mould fluxes to generate TiO 2 into mould fluxes, and mould powder can inevitably pick up Ti-bearing compounds inclusions floating up from steel, which leads to increase of the concentration of TiO 2 in mould flux. This phenomenon can be illustrated by following equation: 4) Increase of TiO 2 concentration due to above reaction could have strong influence on physicochemical properties of mould slag such as viscosity and crystallization ability, and performance of heat transfer and lubricity, which would bring instability and even problems during operation of casting. 4,5) Physicochemical properties of melts strongly depend on the microstructure and investigation of structure characteristics can be employed to explain the changes of physiochemical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation